(untitled) (Clinical Sociology Review, 2023)
The institutionalization process of a discipline can be studied from a set of representative cases on which, although we cannot base ourselves to account for all its complexity, they do allow us to identify the elements involved in that process and the problems to be faced. This work is dedicated, in its first part, to the presentation of the debate around two visions of sociology that coexist and characterize its institutionalization. First, the classic discussion around the dichotomies "theory and technique", "theoretical and applied", "science and profession", "basic research and applied research" is explored, to then address the relevance of applied sociology. Finally, the particular case of the first attempt to institutionalize clinical sociology in Colombia from its inclusion in the study plan of the sociology career of the Universidad del Atlántico is exposed, together with the development of research activities; social outreach activities; internships and degree projects; diploma courses, international seminars, publications and, finally, the creation of a professional association.